Intimate Partner Violence (IPV) in Homosexual Man - Fauziah Mirlavia Aisyah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Violence of homosexual (gay) couples or also known as Intimate Partner Violence (IPV) is a phenomenon that commonly occurs in society. This study aims to observe an image of IPV which occurs in homosexual (gay) community. A measuring instrument used in this research belongs to Black C. Michael, et. al. (2010) for measuring IPV. The research has already done by quantitative study with descriptive type. Respondents in this research are homosexuals (gay) who have a friend date, lover (boyfriend), or ex lover (ex boyfriend). Respondents in this research are about 100 people which consist of 30 people in pilot study and 70 people in field study. The result of this research showed that most of the respondents have already sustained of IPV behavior by his couple. Respondents in this research sustained in the IPV behavior which is actually risky for them. The biggest IPV behaviors happen in psychological aggression, where someone falls on to violence verbally and emotionally. While the smallest IPV behaviors happen in sexual health.